Enantioselective Crystallization of Chiral Inorganic Crystals of ϵ‐Zn(OH)2 with Amino Acids. Issue 47 (9th September 2020) - Otis, Gil; Nassir, Molhm; Zutta, Michael; Saady, Abed; Ruthstein, Sharon; Mastai, Yitzhak
Abstract: Many inorganic materials can form crystals, but little is known about their enantioselective crystallization. Herein, we report on the enantioselective crystallization of ϵ‐Zn(OH)2 (Wulfingite) chiral crystals by using amino acids. Crystals of ϵ‐Zn(OH)2 were crystallized from supersaturated sodium hydroxide and zinc nitrate aqueous solutions in the presence of l ‐ or d ‐arginine. All of the chiral measurements, such as selective chiral adsorption by circular dichroism (CD), chiral chromatography, and polarimetry measurements, clearly show chiral discrimination during the crystallization of ϵ‐Zn(OH)2 . In addition, a new method has been developed for identifying chirality in crystals by using electron paramagnetic resonance (EPR). Although the values of chiral induction of the ϵ‐Zn(OH)2 crystals obtained are somewhat low, these values are still significant because they demonstrate that enantioselectivity during the crystallization of chiral inorganic crystals with chiral additives can be achieved. The method can be applied to many chiral inorganic systems. Understanding and controlling the crystallization of chiral inorganic crystals is important for gaining knowledge on the interaction of chiral molecules with inorganic surfaces. This knowledge can lead to an understanding of basic scientific questions such as the evolution of homochirality in biomolecules and the development of chiral inorganic crystals for a variety of purposes such as asymmetric catalysis and optical applications. Abstract : Chiral crystals of ϵ‐Zn(OH)2 were crystallized from supersaturated aqueous solutions in the presence of l ‐ or d ‐arginine and chiral discrimination was observed during the crystallization. A new method for identifying chirality in crystals by using electron paramagnetic resonance (EPR) has also been developed.